Implications of pronominal variation and forms of treatment in the construction of persons in História da Minha Infância, by Gilberto Amado (Revista de Estudos da Linguagem, 2024)
This paper seek to aim for pronominal variation and forms of treatment in the construction of personas in the memoir literary text, História da Minha Infância (1999), by Gilberto Amado. Thus, we resorted to the notion of persona, worked on in Sociolinguistics both by Eckert (2001, 2003, 2004, 2005) and by Coupland (2001), who argue that style, defined in terms of formality and informality, should to be taken beyond a continuum, and to be observed as a different modus operandi to perform the same task, and the theory of a developed by Brown and Gilman (1960) was taken into account, which is usually referred to as a theory of Power and Solidarity. According to these scholars, such theory would have two principles, power and solidarity, through which they are manifested as existing relationships between interlocutors. This work was also based on the Labovian theory of variation - which takes variation as directly correlated to social factors. Thus, this article takes the approach of style as a factor associated with other factors of a social, historical, economic, cultural, nature, etc. We sought to demonstrate how the social profiles of certain characters are built based on the linkage of specific linguistic variants, which, among other occurrences, denote linguistically marked hierarchical relationships, among ones stand out which symmetrical (equality / affinity) and asymmetric (inferiority and superiority) through the use of pronouns and pronominal forms you, you, you, sir, your lordship, colonel, and directly correlated to the social role played in the society portrayed there.